Analyzing buyer behavior when selecting green criteria in public procurement. Issue 2 (1st March 2017) - Igarashi, Mieko; Boer, Luitzen de; Pfuhl, Gerit
Abstract : Given the complexity of green public procurement, decisions are likely to be driven by bounded rationality. However, we know little about what determines supplier selection criteria in any given situation. This study explores buyer behavior when considering environmental criteria. We first conducted interviews and identified 12 operational procedures used by buyers. We then developed a survey to explore the use of these procedures. Our quantitative analysis suggests that public buyers are motivated by their belief that they can make a difference. This is independent of buyers' experience or gender. However, their occupational position and the nature of a procurement seem to influence how buyers seek information about environmental criteria and which information source(s) they use. The data suggest that four specific decision-making heuristics are associated with the selected operational procedures.